A profile of Mexico's technological agglomerations: The case of the aerospace and nanotechnology industry in Querétaro and Monterrey. (August 2016) - Luna-Ochoa, Sergio Marco A.; Robles-Belmont, Eduardo; Suaste-Gomez, Ernesto
Abstract: This article analyzes the dynamics of emergence of technological clusters in Mexico. In recent years, Mexico has had several initiatives towards the agglomeration of technological capabilities, however, very few cases are successful. The question we are interested in is about how does the technological crowds get configurated. Two Mexican case studies were analyzed in order to identify key endogenous and exogenous factors in the installation and development of technology clusters in the aerospace and nanotechnology. The review of the process of installing both clusters shows the importance of industrial and economic trajectories, the local policy, and the mobilization of local and global actors in the configuration of technological agglomerations. Geographical distances between the technological platforms is important as well, but it requires global players to make the articulation between the local capacities with global trends in emerging technologies. Highlights: We study the dynamics of the processes of installation of technological agglomerations in Mexico. The installation of new technological agglomerations is based on existing industrial and technological capabilities. The local politics and global relations are important elements for the development of emerging technologies. The configurations of technological agglomerations may have distributed and centralized features.